Seroprevalence of leptospiral antibodies among healthy municipal service workers in Selangor - Samsudin, Suhailah; Masri, Siti Norbaya; Tengku Jamaluddin, Tengku Zetty Maztura; Saudi, Siti Nor Sakinah; Md Ariffin, Umi Kalsom; Amran, Fairuz; Osman, Malina (Hindawi Publishing Corporation, 2015)
Introduction. Municipal service workers have been found to have an occupational risk of leptospirosis. Study among municipality workers shows high seropositivity of leptospiral antibodies detected among town cleaners and garbage collectors. Objective. Aims of this study were to determine seroprevalence of leptospiral antibodies and distribution of serovars detected in samples among municipal service workers. Methodology. Cross-sectional study involved 89 municipal service workers in Selangor. Blood samples were taken and serological test was done using MAT following standard procedures. Results. Seropositivity of leptospiral antibodies among municipal service workers was 34.8%. Serovars identified were strains of Sarawak, Copenhageni, Hardjobovis, Lai, Bataviae, Patoc, Celledoni, Hardjoprajitno, Tarrasovi, and Pomona. There were 31 workers with positive leptospiral antibodies. All of them were frequently exposed towards leptospirosis. Significant associations have been reported between seropositivity of leptospiral antibodies with job category () and worker’s nationality () among municipal service workers. Conclusion. High seropositivity of leptospiral antibodies detected among municipal service workers which was associated with job category and nationality of workers. The significant findings from this study suggest that health education programs and safe work practice should be considered to prevent leptospirosis among municipal service workers in future.